The effect of the mixed external donors on the sequence length distribution of polypropylene. Issue 3 (22nd November 2012) - Chang, Hefei; Ren, Shitong; Dang, Xiaofei; Zhang, Liaoyun; Li, Huayi; Hu, Youliang
Abstract The effects of different mixed external donors on the crystallization behavior and sequence length distribution of polypropylene prepared by MgCl2‐supported TiCl4 Ziegler–Natta catalyst were studied through successive self‐nucleation and annealing (SSA) technique. The SSA results show that the crystallization ability and the relative contents of long isotactic sequence length gradually increase with the increase of the relative component of Donor‐1 (cyclohexylmethyldimethoxysilane, dicyclohexyl(dimethoxy)silane, and dipiperidinedimethoxysilane) in the different mixed external donors when the ratio of the mixed external donors/Ti (Si/Ti) is unchanged. The thickness distribution of lamellar also becomes broader, indicating the sequence length distribution of polypropylene gets broader. The crystallization ability and the relative contents of long isotactic sequence length of polypropylene prepared by the mixed cyclohexylmethyldimethoxysilane and n‐propyltriethoxysilane (CN) external donors are lowest. However, the effect of the mixed dicyclohexyl(dimethoxy)silane and n‐propyltriethoxysilane (HN) and the mixed dipiperidinedimethoxysilane and n‐propyltriethoxysilane (PyN) external donors on the crystallization ability and sequence length of polypropylene are more significantly. Especially, the relative content of long isotactic sequence length increases sharply from 0.2 to 27.5% in the polypropylene chain of sample prepared by the mixed PyN external donors when the proportion of Donor 1 is running up to 90%. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013